Evocaciones cervantinas en Tirso - Oteiza, Blanca (2016)
Este trabajo trata de las relaciones, inexistentes, probables o seguras, entre ambos escritores teniendo en cuenta cuatro aspectos: si se conocieron; la presencia de Tirso en Cervantes, la influencia de Cervantes en Tirso y la evocación cervantina en la obra del Mercedario
This article analyses the non-existent, probable or concrete relationships between both writers: Cervantes and Tirso de Molina. The analysis focuses on four aspects: the probability that both of them met and knew each other, the presence of Tirso in the works by Cervantes, the influence of Cervantes in the plays of Tirso and Cervantes evocation in the works of the friar.
Keywords: Molina, Tirso de, -- 1579-1648; Cervantes Saavedra, Miguel de, -- 1547-1616